Knowledge, attitude, and practice towards exclusive breastfeeding and associated factors among adolescent mothers in Nyagatare district, Rwanda - Mugabo, Jackson; Nishimwe, Clemence; Marete, Onesimus; Kubahoniyesu, Theogene (International Journal Of Community Medicine And Public Health, 2025)
Background: Breastmilk provides essential nutrients for infants, supporting growth and protecting against diseases. It also reduces mothers’ risk of ovarian and breast cancer. The World Health Organization recommends exclusive breastfeeding for six months to combat malnutrition, reduce child mortality, and improve maternal health. Methods: This cross-sectional study assessed the knowledge, attitudes, and practices (KAP) of EBF among 194 adolescent mothers in Nyagatare district, eastern province, Rwanda. Results: The findings showed that 85.6% of adolescent mothers had adequate knowledge of EBF, and 78.9% displayed a positive attitude toward it. However, only 27.3% practiced EBF. Key factors positively influencing EBF included primary education [adjusted odds ratio (AOR) =1.161, 95% confidence interval (CI) =1.721-2.319, p=0.009], secondary education (AOR=3.056, 95% CI=2.006-5.542, p=0.013), and a positive attitude (AOR=5.702, 95% CI=1.633-19.91, p=0.006). Employment (AOR=2.041, 95% CI=0.556-7.497, p=0.282) and urban residence (AOR=1.622, 95% CI=1.038–3.089, p=0.007) also increased the likelihood of EBF. Factors reducing EBF odds included an unintended pregnancy (AOR=0.204, 95% CI=0.051-0.817, p=0.025) and having only one child (AOR=0.418, 95% CI=0.037-0.792, p=0.043). Conclusions: Although adolescent mothers generally have high knowledge and positive attitudes toward EBF, actual practice remains low. Addressing barriers through targeted educational and practical interventions is essential to improve EBF rates.